Improving Regional Governance Through Public-Private Partnerships - Vasileva, Elka (UNWE Yearbook, 2020)
The publication analyzes the structure and the functional characteristics of the collective management bodies of regional development in Bulgaria - Regional and District development councils, in relation to the implementation of the partnership principle. Emphasis is placed on the contributions of the participating stakeholders: socio-economic partners, non-governmental organizations, academic circles, civil society associations, etc. Discussing opportunities for improving regional management by building public-private institutional partnerships within the collegiate bodies surveyed.